Sustainable development in buildings (2010)
In  this document  two  topics are exposed:  (1) how  the problems of  the energy consumption and of  the polluting emissions  of  the  current  constructions  they  can  be  reduced with  the  concept  green  building,  and  (2)  how  the sustainable  applications,  implemented  in  other  countries,  they  could  generate  fnancial  important  savings  and sustainability during  the use of  the Edifcio Eléctrica 2 of  the Universidad  Industrial de Santander  that  is  in  the process of design due to two factors: the decrease in the electric power demand and the use of the renewable energies in place. The review of the state-of-the-art, has as central aspects: the sustainable development, the exergy concept and the green building. This analysis of the information will allow establish the relevant aspects to take into account in the technical specifcations for the future design of the Edifcio Eléctrica 2.